2017
DOI: 10.1080/17429145.2017.1316527
|View full text |Cite
|
Sign up to set email alerts
|

Influence of plant-growth-promoting bacteria on germination, growth and nutrients’ uptake ofOnobrychis sativaL. under drought stress

Abstract: The study was conducted to investigate the effect of growth-promoting bacteria (Azotobacter vinelandii = A, Pantoea agglomerans + P. putida = P, combined A + P, control) on the germination, growth and nutrient uptake of Onobrychis sativa L. under drought stress (field capacity (FC), 0.7 FC, 0.4 FC). The results showed that the highest and lowest germination rate (GR) was related to the P and control treatments in FC level, respectively. The maximum root and shoot length at the FC level was related to the treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
25
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(31 citation statements)
references
References 31 publications
(28 reference statements)
5
25
0
1
Order By: Relevance
“…Home soil microbiota promoted germination of the legume irrespective of the watering treatment, which supports our argument that the legume would be more dependent on co-evolved soil microbiota than the grass and forb. These results support previous research that found soil and rhizospheric rhizobial bacteria might enhance germination through the production of enzymes and hormones (Kremer 1993, Requena et al 1997, Shweta et al 2008, Miransari and Smith 2009, Delshadi et al 2017a, b, Lozano et al 2017 and that inoculum paired with plants from the same location further promotes these positive effects on germination (Requena et al 1997). The significantly lower germination with away soil microbiota in drier conditions suggests that soil microbiota that promote germination of the legume were absent or had lower activity in the away soil relative to the home soil microbiota.…”
Section: Germinationsupporting
confidence: 91%
“…Home soil microbiota promoted germination of the legume irrespective of the watering treatment, which supports our argument that the legume would be more dependent on co-evolved soil microbiota than the grass and forb. These results support previous research that found soil and rhizospheric rhizobial bacteria might enhance germination through the production of enzymes and hormones (Kremer 1993, Requena et al 1997, Shweta et al 2008, Miransari and Smith 2009, Delshadi et al 2017a, b, Lozano et al 2017 and that inoculum paired with plants from the same location further promotes these positive effects on germination (Requena et al 1997). The significantly lower germination with away soil microbiota in drier conditions suggests that soil microbiota that promote germination of the legume were absent or had lower activity in the away soil relative to the home soil microbiota.…”
Section: Germinationsupporting
confidence: 91%
“…Furthermore, PGPR-inoculated plants were successful in increasing the nitrogen, phosphorus, and potassium uptake into plant biomass [44,46]. Under water deficit, nutrient content (N-P-K) of plant biomass was improved when plants were treated with PGPR, perhaps owing to incremental root growth and root number that exploited more soil volume for efficient absorption of available essential nutrients [47], thus leading to higher biomass production [1]. These results agree with those obtained in [48], who found that plants inoculated with PGPR in soils with a low availability of the essential elements led to increased N, P, and K uptake due to their increased content in the soil after inoculation compared to non-inoculated plants because of the pivotal impact of root morphology and expansion of the root hairs.…”
Section: Discussionmentioning
confidence: 99%
“…Motility and attachment through biofilm formation also give selective advantage to pathogenic bacteria and are known characteristics of P. syringae [64,65]. To confirm these phenotypes, we first identified motility genes in both organisms, which had nearly 100% conservation to the P. syringae pv.…”
Section: Pathogenicity Of P Syringae Isolatesmentioning
confidence: 99%